Stabilization of Gold in Zeolites with Various Structural and Ionic Properties; Advanced Micro- and Mesoporous Materials - Gurin V.; Tuzovskaya I.; Bogdanchikova N.; Pestryakov A. N. Aleksey Nikolaevich; Avalos M.; Farías M. H. (2008, 2008)
UV/Vis absorption spectra of gold species are studied for a series of Aumordenites derived through the ion-exchange for mordenites with various SiO2/Al2O3 molar ratio and different cations. A series of zeolites with the size of intracrystalline cavities ranged from ~4 2 through ~12 2 show the dramatic effect of the zeolite type upon appearance of the reduced gold species. Quantum chemical calculations of both geometry and electronic transitions support the model of Au8 clusters within the zeolites under the condition of geometrical matching with the cavities.